Adsorption of multiple H2 molecules on the complex TiC6H6: An unusual combination of chemisorption and physisorption. (15th March 2019) - Ma, Li-Juan; Wang, Jianfeng; Han, Min; Jia, Jianfeng; Wu, Hai-Shun; Zhang, Xiang
Abstract: The hydrogen physisorption properties of diverse examples of Ti-decorated six-membered carbocycles have been established and intensively investigated. However, fewer investigations have been devoted to the chemical reactions occurring during the process of hydrogen storage. Herein, for the first time, a variety of plausible hydrogenation intermediates and physisorption complexes involving multiple H2 molecules on the complex TiC6 H6 has been investigated simultaneously. The relative Gibbs free energies of TiC6 H6 -nH2 (n = 1–4) isomers and the minimum-energy pathways of the successive hydrogenation steps show that the overall reactions to give the hydrogenation product TiC6 H11 -3H is exothermic by 11.07 kcal/mol in terms of ΔG (298.15 K). It indicates that a facile switch of hydrogen addition and release with superior capacity of 6.02 wt % can be quickly achieved with simply regulated by increasing/decreasing the hydrogen pressure, which is consistent with the recent experiment on hydrogen adsorption in TiC6 H6 at room temperature. The physisorption processes show that three H2 molecules can be efficiently trapped below 210 K and desorbed completely at 935 K. More importantly, chemisorption and physisorption will convert in certain circumstances, which indicates that the mechanism of the bonding of H2 molecules on TiC6 H6 is an unusual combination of chemisorption and physisorption. Graphical abstract: Image 1 Highlights: Chemisorption capacity of 6.02 wt % for TiC6 H6 can be achieved at room temperature. Three H2 molecules are trapped under 210 K and desorbed completely at 935 K. Chemisorption explains the experimental results perfectly rather than physisorption. Chemisorption and physisorption will convert in certain circumstances. CH2 groups in hydrogenation intermediates tend to connect adjacently.